1989
DOI: 10.1093/carcin/10.9.1595
|View full text |Cite
|
Sign up to set email alerts
|

Inositol-phosphate-induced enhancement of natural killer cell activity correlates with tumor suppression

Abstract: In recent studies, we have demonstrated that inositol hexaphosphate (InsP6) inhibits experimental colon carcinogenesis. Since natural killer (NK) cells are involved in tumor cell destruction, we investigated the effect of InsP6 on murine NK cell activity. We show that; (i) 1,2-dimethylhydrazine (DMH), a colon carcinogen, depresses NK activity; (ii) in vivo treatment of mice with InsP6 enhances baseline NK activity and reverses DMH-induced depressed NK activity with an inverse correlation (r = -0.9811) with tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 0 publications
1
47
1
Order By: Relevance
“…Vucenik et al (173) demonstrated antitumor activity of phytic acid in murine-transplanted and metastatic fibrosarcoma in mice, while Jariwalla et al (174) proposed that dietary phytate nullified the tumor-potentiating effects induced by MgO in the rat, and Hirose et al (175) found that phytic acid also inhibited the development of carcinogenesis in the liver. Phytic acid has been shown to enhance natural killer cell activity, which further correlated with tumor suppression (176), and it may also be involved in the enhancement of the bacterial killing capacity of the host (177). Furthermore, phytic acid has been shown to reduce the cell proliferation rate in human cancer cell lines in vitro (178)(179)(180).…”
Section: Anticancer Functions Of Myoinositol Phosphatesmentioning
confidence: 98%
“…Vucenik et al (173) demonstrated antitumor activity of phytic acid in murine-transplanted and metastatic fibrosarcoma in mice, while Jariwalla et al (174) proposed that dietary phytate nullified the tumor-potentiating effects induced by MgO in the rat, and Hirose et al (175) found that phytic acid also inhibited the development of carcinogenesis in the liver. Phytic acid has been shown to enhance natural killer cell activity, which further correlated with tumor suppression (176), and it may also be involved in the enhancement of the bacterial killing capacity of the host (177). Furthermore, phytic acid has been shown to reduce the cell proliferation rate in human cancer cell lines in vitro (178)(179)(180).…”
Section: Anticancer Functions Of Myoinositol Phosphatesmentioning
confidence: 98%
“…Maybe, it blocks sprouting of new capillaries around newly forming uncontrolled cell growth by making phosphorous and other minerals less bioavailable, as angiogenesis is an energy consuming process and may only flourish if required nutrients are available. It is likely that in addition to the inhibition of iron-catalyzed oxidative damage, other pathways such as the activation of immune competent cells (Baten et al, 1989), as well as the participation of inositol phosphates in signal transduction, cell division and differentiation (Shamsuddin, 1992) are also responsible for beneficial effects of dietary phytate in cancer prevention (Rimbach and Pallauf, 1998).…”
Section: Chelating and Antioxidant Properties Of Phytic Acidmentioning
confidence: 99%
“…The ability of phytic acid to reverse DMBA induced-proliferative changes in rats not only agrees with previous reports in experimental skin, colon and breast carcinogenesis models but also suggest its anti-proliferative properties. [21][22][23][24] This antiproliferative effect of IP-6 may be due to its ability to: (1) enhance baseline Natural Killer cell activity with subsequent destruction of the transformed cells; 21 (2) downregulate genes involved in transcription and cell cycle regulation and to upregulate cell cycle inhibitors 25 and (3) induce apoptotic machinery and to inhibits cell survival signaling. 26 The ability of IP-6 to induce apoptotic activity in our series is in accord with previous studies.…”
Section: Discussionmentioning
confidence: 99%